Thermal conditions for stopping pyrolysis of forest combustible material and applications to firefighting; Thermal Science; Vol. 21, iss. 6, pt. A - Zhdanova A. O. Alena Olegovna; Kuznetsov G. V. Geny Vladimirovich; Legro J. K. Ch. Zhan Klod Chislan; Strizhak P. A. Pavel Alexandrovich (2017, 2017)
Title screen